L’impossible désappartenance : le paysan des Hautes Terres d’Écosse et les clearances du dix-neuvième siècle - Christian Auer (Cahiers Victoriens et Edouardiens)
In the middle of the nineteenth century, at a time when the Highlands of Scotland were being wounded by the clearances, the traditional clan had all but disappeared and the chiefs had abandoned one of their most fundamental functions, the protection of the community from potential external threats. Yet, the notion of clan was still deeply imprinted in the Highland peasant’s mind, which made it all the more difficult for him to criticise the chief’s involvement in the economic process that was tearing the community apart. For the peasant to do that would also have amounted to nothing more than questioning his own existence and identity.